Analysis of Ability to Understand Text Reading on Students of English Education Study Program - Kemala S., Sarma Dewi; Marpaung, Devi Anisa (Future Science / FSH-PH Publications, 2022)
This research was conducted with the title Analysis of the second semester students' ability of the English Education Study Program in understanding reading texts. The purpose of this research is to examine the students' ability to understand the text. This study uses a qualitative method. The population used is the second semester students of HKBP Nommensen Pematangsiantar University for the 2020/2021 academic year. The sample taken is 32 people. The research data were collected from the given text. During the test, 30 questions were given. The type of test given is an objective test. After collecting the data, the writer then analyzed the students' scores. From these students, it was found that almost all students could not understand the text. There are 19 students (59.37%) who score below 65 and that makes them still need more attention than to help them improve their ability to understand the text.